Flat Tax Reform.The Baltics 2000-2007 - Helmuts Āzacis; Max Gillman (Hungarian Academy of Sciences, Institute of Economics, 2008)
The paper presents an endogenous growth economy with a representation of the tax rate system in the Baltic countries. Assuming that government spending is a given fraction of output, the papershows how a flat tax system balanced between labor and corporate tax rates can be second best optimal. It then computes how actual Baltic tax reforms from 2000 to 2007 affect the growth rate and welfare, including transition dynamics. Comparing the actual reform effects to hypothetical tax experiments, it results that equal flat tax rates on personal and corporate income would have increased welfare in all three Baltic countries by 24% more on average than the actual reforms. This shows how equal, balanced, flat rate taxes can be optimal in both theory and practice. Further, movement towards a more equal balance between labor and capital tax rates, through changing just one tax rate, achieved almost as high or higher utility gains as in actual law for all three countries under both open and closed economy cases. This shows benefits of moving towards the optimum.
Keywords: E13; H20; O11; O14; 330; tax reform; endogenous growth; transitional dynamics; flat taxes; Steuerreform; Flat Tax; Wirkungsanalyse; Nordosteuropa